ILC2 Proliferated by IL-33 Stimulation Alleviates Acute Colitis in Rag1-/- Mouse through Promoting M2 Macrophage Polarization - Yong You; Xiaoqing Zhang; Xiao Wang; Dan Yue; Fanxiang Meng; Junfeng Zhu; Yuanyuan Wang; Xun Sun (Journal of Immunology Research)
This study was to identify functions of ILC2, a newly found innate lymphoid cell which mainly locates in mucosa organs like lungs and intestines, in IBD. We injected rIL-33 protein to C57/BL6 mouse to explore how IL-33 induces ILC2 proliferation. The results showed that ILC2 reached a proliferation peak at day 5 and expressed multiple surface markers like CD127, C-kit, CD69, CD44, ST2, CD27, DR3, MHCII, and CD90.2. ILC2 also expressed high quantity of IL-13 and IL-5 and few IL-17A which indicates a potentially immunological function in IBD development. Afterwards, we transferred sort purified ILC2 to Rag1-/- mouse given DSS to induce acute colitis in order to explore the innate function of ILC2. Data showed that ILC2 alleviates DSS-induced acute innate colitis by repairing epithelial barrier and restore body weight. Furthermore, we found that ILC2 can cause macrophages polarizing to M2 macrophages in the gut. Therefore, we concluded that ILC2 played a therapeutic role in mouse acute colitis.